Effect of skilled and unskilled training on nerve regeneration and functional recovery - Pagnussat A.S. (2012)
The most disabling aspect of human peripheral nerve injuries, the majority of which affect the upper limbs, is the loss of skilled hand movements. Activity-induced morphological and electrophysiological remodeling of the neuromuscular junction has been shown to influence nerve repair and functional recovery. In the current study, we determined the effects of two different treatments on the functional and morphological recovery after median and ulnar nerve injury. Adult Wistar male rats weighing 280 to 330 g at the time of surgery (N = 8-10 animals/group) were submitted to nerve crush and 1 week later began a 3-week course of motor rehabilitation involving either "skilled" (reaching for small food pellets) or "unskilled" (walking on a motorized treadmill) training. During this period, functional recovery was monitored weekly using staircase and cylinder tests. Histological and morphometric nerve analyses were used to assess nerve regeneration at the end of treatment. The functional evaluation demonstrated benefits of both tasks, but found no difference between them (P > 0.05). The unskilled training, however, induced a greater degree of nerve regeneration as evidenced by histological measurement (P < 0.05). These data provide evidence that both of the forelimb training tasks used in this study can accelerate functional recovery following brachial plexus injury.